Propagation of Computer Virus under Human Intervention: A Dynamical Model - Chenquan Gan; Xiaofan Yang; Wanping Liu; Qingyi Zhu; Xulong Zhang (Discrete Dynamics in Nature and Society)
This paper examines the propagation behavior of computer virus under human intervention. A dynamical model describing the spread of computer virus, under which a susceptible computer can become recovered directly and an infected computer can become susceptible directly, is proposed. Through a qualitative analysis of this model, it is found that the virus-free equilibrium is globally asymptotically stable when the basic reproduction number R0≤1, whereas the viral equilibrium is globally asymptotically stable if R0>1. Based on these results and a parameter analysis, some appropriate measures for eradicating the spread of computer virus across the Internet are recommended.